Prevalence of Workplace Violence of Emergency Medical Staff and Relevant Factors in Sanandaj, Iran in 2016 - Abdorraim Afkhamzadeh; Namam-ali Azadi; Zahra Farahmandian; Amjad Mohamadi-bolbanabad (Kurdistan University of Medical Sciences, 2018)
Background & Aim: In the past years, workplace violence in the area of health has been reported with an upward trend. This study aimed to evaluate the frequency of dealing with workplace violence in emergency medical staff of Sanandaj, Iran and relevant factors. Materials & Methods: This descriptive, analytical, and cross-sectional research was conducted in the emergency medical centers of Sanandaj in 2016. Considering the limited research population, census method was applied and all 126 staff of these centers were selected. Data were collected via a self-report questionnaire. In addition, data analysis was performed in SPSS version 20 using Chi-square and Fisher’s exact tests. Results: In this research, 84% (95% CI=75-90) of the participants had an experience of workplace violence in the past year, 42% (95% CI=32-52) of which has been physical and 81% (95% CI=72-88) has been verbal violence. In addition, 59.4% (N=47) of the staff reported the source of violence to be the companions of patients. Moreover, 87% of the participants believed that there is no proper procedure to report workplace violence. Results were indicative of no significant relationship between workplace violence in the emergency medical staff and variables of age, marital status, work experience, and having work shift (P>0.05). Conclusion: According to the results of the study, there is an alarmingly high rate of workplace violence in the emergency medical centers of Sanandaj. This level of violence might reduce care quality and increase occupational stress. Considering the high rate of accidents in Iran and the necessity of composure for the staff, management interventions (e.g., public community education, creation of a suitable report system for the personnel and review of reports) are required to improve this area.